PRESCRIPTION ANALYSIS OF HYPERTENSIVE PATIENTS AND AWARENESS AMONG PHYSICIAN REGARDING ANTIHYPERTENSIVE DRUG - J., PATIL P.; S., PATIL V.; P., BHORE (International Journal of Current Pharmaceutical Research, 2020)
Objective: This study was conducted to analyze prescriptions of the hypertensive patient and to determine the awareness of physicians regarding antihypertensive drugs. Methods: Prepare a questionnaire by the pilot study on five physicians. Review and finalized the questionnaire after discussion with pharmacologist. The answers were seek for awareness. Moreover the prescription of 30 patients was collected from the same physician who has undertaken the awareness regarding Antihypertensive Drugs. Study was conducted during Oct-2019 to Dec 2019. Results: Average 83% awareness was found in the physician regarding antihypertensive drugs. Lack of awareness regarding diabetes and in ulcer patients was observed. Highest drug is given i.e. β blockers in antihypertensive patients. To determine the irrationality in the prescription of hypertensive patients. Conclusion: To determine the FDC`s given to hypertensive patients. To determine the type of antihypertensive drugs given to patients.